2017
DOI: 10.1093/jxb/erx211
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and metabolic acclimation to repeated drought events play key roles in drought tolerance in coffee

Abstract: Over the last decades, most information on the mechanisms underlying tolerance to drought has been gained by considering this stress as a single event that happens just once in the life of a plant, in contrast to what occurs under natural conditions where recurrent drought episodes are the rule. Here we explored mechanisms of drought tolerance in coffee (Coffea canephora) plants from a broader perspective, integrating key aspects of plant physiology and biochemistry. We show that plants exposed to multiple dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 60 publications
6
50
0
3
Order By: Relevance
“…For example, Marraccini et al (2012) and Vieira et al (2013) compared variations in the physiological and gene expression responses of drought tolerant and drought sensitive Robusta varieties, and suggested that the drought tolerant clones had subtle differences in ABA signaling and a better induction of the coffee antioxidant and osmoprotection systems. In another examination of the physiological effects induced by drought, (Menezes-Silva et al 2017) explored the effect of repeated rounds of water deficit and recovery on one Robusta variety. The physiological data obtained indicated that plants exposed to multiple water deficit events had higher photosynthetic rates then control plants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Marraccini et al (2012) and Vieira et al (2013) compared variations in the physiological and gene expression responses of drought tolerant and drought sensitive Robusta varieties, and suggested that the drought tolerant clones had subtle differences in ABA signaling and a better induction of the coffee antioxidant and osmoprotection systems. In another examination of the physiological effects induced by drought, (Menezes-Silva et al 2017) explored the effect of repeated rounds of water deficit and recovery on one Robusta variety. The physiological data obtained indicated that plants exposed to multiple water deficit events had higher photosynthetic rates then control plants.…”
Section: Introductionmentioning
confidence: 99%
“…Means followed by the same letter, uppercase in the line and lowercase in the column belong to the same cluster by the Scott-Knott test (p < 0.05). Coffee plants show anatomical and physiological changes related to the existing limiting growing factors such as water stress and radiation exposure levels (MENEZES-SILVA et al, 2017). In this study, difference in the leaf water potential, tissue spacing, and vascular bundles were found in plants grown under water restrictions.…”
Section: Resultsmentioning
confidence: 54%
“…In addition to intensity and duration, the frequency of drought events appears to be a predominant factor in forest dieback events, yet it is rarely taken into account in climate models. In fact, few studies to date have focused on the behavior of plants subjected to cyclical drought episodes, even though this is a more common situation than isolated events (Menezes‐Silva et al, ). Recent studies have also shown that after exposure to severe drought, years may be required for several plant communities to fully recover their physiological processes (e.g., growth rates), making them even more vulnerable to further drought episodes (Anderegg, Schwalm, et al, ).…”
Section: Main Drivers Of Forest Dieback Under a Scenario Of Climate Cmentioning
confidence: 99%
“…For some species, high temperatures induce the reduction in stomatal conductance (g s ), reducing leaf transpiration and increasing leaf temperature, which may lead to deeper reductions in photosynthesis (A) and increases in photorespiration (P R ) and respiration (R) rates, further intensifying the negative carbon balance induced by drought. For other species, high temperatures increase the stomatal conductance and leaf transpiration, further increasing the tension in xylem vessels induced by drought, leading to higher vulnerability to cavitation and hydraulic failure studies to date have focused on the behavior of plants subjected to cyclical drought episodes, even though this is a more common situation than isolated events (Menezes-Silva et al, 2017). Recent studies have also shown that after exposure to severe drought, years may be required for several plant communities to fully recover their physiological processes (e.g., growth rates), making them even more vulnerable to further drought episodes (Anderegg, Schwalm, et al, 2015).…”
Section: Droughtmentioning
confidence: 99%